Severe Nonspecific Interstitial Pneumonia (NSIP) in an Adolescent. (9th August 2022) - Cerro Chiang, Giuliana; Lee, Christopher; Marchevsky, Alberto; Lewis, Michael I.
Abstract : Childhood interstitial lung disease (chILD) is remarkably rare with a reported prevalence from 0.13 per 100, 000 children under 17 years to 16.2 per 100, 000 children under 15 years of age (Kornum et al., 2008). Here, we present a case of a 15-year-old with subacute hypoxemic respiratory failure, admitted to the critical care unit. Her imaging on admission showed bilateral interstitial infiltrates; her laboratory workup, including autoimmune serologies, was unrevealing. A bronchoscopy revealed the diagnosis of nonspecific interstitial pneumonia. She had a partial recovery after a course of steroids.